Family mealtime practices of selected grade four students in Quezon City - Batac, Edcille Louise T.; Chua, Consuelo Trio (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study described the mealtime practices of selected low and middle income families in Quezon City. An interview was conducted among 38 fourth grade students from San Vicente Elementary School and University of the Philippines Integrated School to determine their family mealtime practices and attitudes, and to compare these in terms of socio-economic status. Results showed similarities and differences in the mealtime practices between low and middle income families. As for the similarities, hand washing and praying were the most followed table rules. Furthermore, mothers and fathers normally cook the food, while their children are assigned in the preparation and cleaning of the dining table. Both socio-economic groups follow a basic table setting arrangement. As for differences, middle income families spend more mealtimes together compared with low income families. With regards to their seating arrangement, most of the low income families follow the circular arrangement, while the traditional seating arrangement was common among the middle income families. The common mealtime conversation topics of low income families include academics, health, and future plans, while entertainment, future plans, and academics were mostly discussed by the middle income families. Lastly, most of the respondents from low and middle income families were happy with their table rules, conversation topics and with their practice of spending meals together with their family. The study concludes that families still spend meals together frequently. Hence, this means that there are more opportunities to strengthen the family relationship and develop the social, intellectual, and socio-cultural skills of the children.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Food habits -- Philippines